The mediating effect of utility of informal organization between participation of informal organization and job satisfaction: 비공식조직의 순기능적 유용성의 매개효과를 중심으로 - Kang, Minji; Lee, Kyehoon; Moon, Kwangsu; Oah, Shezeen (Korean Journal of Industrial and Organizational Psychology, 2012)
The purpose of the present study was to examine the influence of participation in informal organization on the job satisfaction. This study also attempted to find out the mediating effects of utility of informal organization in the relationship between participation and job satisfaction. Based on previous research, we classified utility into affective, communication, instrumental utility. Data were collected from 206 workers employed in various organizations. It was found that participation in informal organization were significantly related with high job satisfaction. In addition, the toeal utility were fully mediating the relationship between participation and job satisfaction. Affective, communication utilities had full mediating effects and instrumental utility had a partial mediating effect. This finding suggest that organizations should actively support informal organizations and find the way to encourage employees to participate informal organizations.